Coronary artery calcification is increased in patients with COPD and associated with increased morbidity and mortality - Williams, Michelle C; Murchison, John T; Edwards, Lisa D; Agustí, Alvar; Bakke, Per; Calverley, Peter M A; Celli, Bartolome; Coxson, Harvey O; Crim, Courtney; Lomas, David A; Miller, Bruce E; Rennard, Steve; et al. (Thorax, 2014)
Background Coronary artery calcification is pathognomonic of coronary artery disease (CAD). Whether CAD in patients with COPD is linked to lung function, functional capacity and/or clinically relevant outcomes is unknown. The objective was to assess the association between CAD and disease severity, functional capacity and outcomes in patients with COPD. Methods Coronary artery calcium score (CACS; Agatston score) was measured using chest CT in patients with COPD, smokers with normal spirometry and non-smokers from the Evaluation of COPD Longitudinally to Identify Predictive Surrogate Endpoints (ECLIPSE) study. Results CACS was measured in 942 subjects: 672 with COPD (mean age±SD, 63±7 years; FEV1 49±16% predicted), 199 smokers with normal spirometry (54±9 years; FEV1 110±12% predicted) and 71 non-smokers (55±9 years; FEV1 114±14% predicted). CACS was higher in patients with COPD than smokers or non-smokers (median (IQR), 128 (492) vs 0 (75) vs 0 (3) Agatston units (AU), p<0.001). In patients with COPD, CACS correlated with age, pack-years, 6 min walking distance, modified Medical Research Council Dyspnoea score and circulating levels of interleukin (IL)-6, IL-8, Clara Cell protein 16, surfactant protein D and peripheral blood neutrophil count, but not with emphysema, exacerbation frequency, % predicted FEV1 or decline in FEV1. CACS was higher in patients with COPD who died than in those who survived until 3-year follow-up (CACS 406 vs 103 AU, p<0.001), and was associated with mortality in a Cox proportional hazards model (p=0.036). Conclusions Patients with COPD have more CAD than controls and this is associated with increased dyspnoea, reduced exercise capacity and increased mortality. These data indicate that the presence of CAD in patients with COPD is associated with poor clinical outcomes.